Development of fuelling protocols for gaseous hydrogen vehicles: a key component for efficient and safe hydrogen mobility infrastructures. Issue 1 (9th February 2023) - Xu, Zhuang; Dong, Wenping; Zhao, Yuejing; Dong, Hui; He, Guangli
Abstract: Large-scale applications of fuel-cell vehicles (FCVs) are of vital importance to reduce emissions of greenhouse gases in the transportation sector, especially in the heavy-duty and long-distance scenarios. Efficient fuelling for the on-board gaseous hydrogen cylinders of an FCV is essential to achieve a fuelling experience that is comparable to that of traditional fossil-fuel-powered vehicles. However, the heating effect during refuelling leads to potential safety issues when the hydrogen temperature in the cylinder exceeds 85°C. Therefore, fuelling protocols are critical to ensure the efficiency and safety of the hydrogen mobility infrastructure. In this paper, the fuelling protocols for FCV vans and buses with type III cylinders were developed and the pre-cooling temperatures were optimized to minimize the energy consumption. Their performance was demonstrated with a 35-MPa hydrogen fuelling station. We found that FCV vans and buses can be safely refuelled in 3 or 5 minutes at a minimum, respectively, demonstrating a fuelling experience that is similar to that of traditional vehicles. Abstract : Hydrogen fuelling protocols for fuel-cell vans and buses with type III cylinders were developed and optimized to minimize energy consumption. Experiments with a 35-MPa hydrogen fuelling station showed that vans or buses could be safely refuelled in 3 or 5 minutes, demonstrating a fuelling experience similar to that of traditional vehicles. Graphical Abstract: